Implication of miR-122, miR-483, and miR-335 Expression Levels as Potential Signatures in HCV-Related Hepatocellular Carcinoma (HCC) in Egyptian Patients - Elfert, Ashraf Y.; Salem, Amel; Abdelhamid, Amr M.; Salama, Ahmad; Sourour, Doaa A.; Shaker, Olfat; Keshk, Mofida (Frontiers in Molecular Biosciences, 2022)
Hepatocellular carcinoma (HCC) is the second most common cause of cancer-related death worldwide with chronic hepatitis C virus (HCV) infection as a major risk factor of HCC. Circulating microRNAs are deregulated in HCC and are candidate biomarkers. The aim of this study was to explore the expression profile of miRNA-122, MiR-483, and MiR-335 in the serum of HCV-related Hepatocellular Carcinoma (HCC). 90 HCV-related Hepatocellular Carcinoma (HCC), 90 nonmalignant HCV patients and 60 healthy controls were included. Serum microRNAs were measured by qRT-PCR custom array. The expression levels of miR-122 and miR-483 were upregulated in HCC patients while miR-335 expression level was downregulated versus controls and HCV groups. Receiver operating characteristic curve (ROC) analysis was created to examine miRNAs. MiR-483 presented the best diagnostic potential because it showed the highest diagnostic accuracy for HCV related HCC patients from control (AUC = 0.98) with sensitivity 100%. Moreover, obvious prognostic power in distinguishing HCV from HCC (AUC = 0.95) with sensitivity 88%. In conclusion, studied micro-RNAs (miR-122, miR-483, and miR-335) could serve as potential non-invasive early diagnostic biomarkers for HCC, we identified a panel of three serum microRNAs with high accuracy in HCC diagnosis. Additional studies are required to confirm this panel and test its prognostic significance.